Pendidikan dan Pekerjaan Ibu Merupakan Faktor yang Berpengaruh Langsung terhadap Praktik Pemberian Makanan pada Anak (PMBA): Mother's Education and Work Are Factors That Have a Direct Influence on The Practice of Child Feeding (PMBA) - Isfaizah; Ari Widyaningsih; Moneca Diah Listiyaningsih (Indonesian Journal of Midwifery (IJM), 2024)
Complementary feeding practices can cause malnutrition which contributes to the incidence of child malnutrition. Many factors influence complementary feeding (CF) practices, including biological factors, socio-economic status, and local culture. This research aims to analyze the influence of bio-socioeconomic status and culture on Complementary Feeding (CF) practices in Semarang Regency. The research design is observational analytic with a cross-sectional approach. The population is all mothers who have toddlers aged 12-60 months in West Ungaran District, totaling 776 toddlers. The sampling technique used was accidental sampling with a sample size of 198 respondents. The independent variables are the mother's age, child care provider, number of children, mother's education, mother's occupation, child's gender, child order, and culture while the dependent variable is child feeding practices (IYCF) which are measured using the Complementary Feeding Practice Questionnaire (CFPQ), while the independent variable uses a questionnaire whose validity and reliability have been tested. The data analysis that will be used is univariate analysis, bivariate analysis and multivariate analysis with logistic regression. The results of the bivariate analysis showed that the age of the mother, child caregiver, number of children, order of children, gender of the child and culture were not significant to CF practices. Multivariate analysis with logistic regression shows that maternal education and maternal employment influence CF practices, where mothers with higher education tend to provide better CF practices by 2.77 than mothers with low education. Working mothers also tend to increase CF practices better by 2.17 compared to mothers who do not work. It is best for health workers and educational institutions to work together to increase the accessibility of information about good CF practices for children.   Abstrak Praktik pemberian makan yang kurang tepat dapat menyebabkan malnutrisi yang berkontribusi dalam kejadian gizi buruk anak. Banyak faktor yang mempengaruhi praktik Pemberian Makan Bagi Anak (PMBA) diantaranya faktor biologis, sosial ekonomi status dan budaya setempat. Penelitian ini bertujuan untuk menganalisis pengaruh bio-sosial ekonomi status dan  budaya dengan praktik Pemberian Makan Bagi Anak (PMBA) di Kabupaten Semarang. Desain penelitian adalah analitik observasional dengan pendekatan cross-sectional. Populasi adalah seluruh ibu yang memiliki balita usia 12-60 bulan di Kecamatan Ungaran Barat sebanyak 776 balita. Teknik pengambilan sampel yang digunakan adalah accidental sampling dengan jumlah sampel sebesar 198 responden. Variabel independen adalah umur ibu, pengasuh anak, jumlah anak, pendidikan ibu, pekerjaan ibu, jenis kelamin anak, urutan anak dan budaya sedangkan variabel dependennya adalah praktik pemberian makan bagi anak (PMBA) yang diukur dengan menggunakan Complementary Feeding Practice Questionare (CFPQ), sedangkan variabel independen menggunakan kuesioner yang telah teruji validitas dan reliabilitasnya. Analisis data yang akan digunakan adalah analisis univariat, analisis bivariat dan analisis multivariat dengan regresi logistic. Hasil analisis bivariat diperoleh umur ibu, pengasuh anak, jumlah anak, urutan anak, jenis kelamin anak dan budaya tidak signifikan dengan praktik PMBA. Analisis multivariat dengan regresi logistik menunjukkan bahwa pendidikan ibu dan pekerjaan ibu berpengaruh terhadap praktik PMBA, di mana ibu dengan pendidikan tinggi cenderung memberikan PMBA yang lebih baik sebesar 2,77 dibandingkan ibu berpendidikan rendah. Ibu yang bekerja juga cenderung meningkatkan praktik PMBA yang lebih baik sebesar 2,17 dibandingkan ibu yang tidak bekerja. Sebaiknya tenaga kesehatan dan instansi pendidikan bersinergi dalam meningkatkan keterjangkauan informasi tentang praktik PMBA yang baik bagi anak.